2020
DOI: 10.3389/fonc.2019.01464
|View full text |Cite
|
Sign up to set email alerts
|

Improving Treatment Response Prediction for Chemoradiation Therapy of Pancreatic Cancer Using a Combination of Delta-Radiomics and the Clinical Biomarker CA19-9

Abstract: Recently we showed that delta radiomics features (DRF) from daily CT-guided chemoradiation therapy (CRT) is associated with early prediction of treatment response for pancreatic cancer. CA19-9 is a widely used clinical biomarker for pancreatic cancer. The purpose of this work is to investigate if the predictive power of such biomarkers (DRF or CA19-9) can improve by combining both biomarkers. Daily non-contrast CTs acquired during routine CT-guided neoadjuvant CRT for 24 patients (672 datasets, in 28 daily fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 30 publications
(34 reference statements)
0
30
0
1
Order By: Relevance
“…Another application of radiomics not explored by our study is the use of delta-radiomics to assess treatment response [13]. By comparing the differences in patients' longitudinal radiomic data as they progress through treatment, researchers were able to assess treatment response earlier and more reliably than current methods of assessment, such as trending CA-19-9, in pancreatic cancer [14]. A recent study performed by Nardone et al further suggests that the use of radiomics in tracking treatment response is better accomplished by the analysis of delta-radiomics than of a single radiomic dataset [15].…”
Section: Discussionmentioning
confidence: 97%
“…Another application of radiomics not explored by our study is the use of delta-radiomics to assess treatment response [13]. By comparing the differences in patients' longitudinal radiomic data as they progress through treatment, researchers were able to assess treatment response earlier and more reliably than current methods of assessment, such as trending CA-19-9, in pancreatic cancer [14]. A recent study performed by Nardone et al further suggests that the use of radiomics in tracking treatment response is better accomplished by the analysis of delta-radiomics than of a single radiomic dataset [15].…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, further evaluation needs to be carried out in translating such research into clinical practice because most literature in the field had a multi-localization/multi-type tumor cohort design. Deltaradiomics features (Delta-RFs) which capture therapy-induced changes in radiomics features are now being evaluated as a complement to Response Evaluation Criteria in Solid Tumor (RECIST) criteria for monitoring therapeutic response in several tumor types (25)(26)(27)(28)(29)(30)(31). Khorrami et al showed preliminary evidence for clinical use of Delta-radiomics calculated from contrast-enhanced CT images as predictive biomarkers of response to ICIs therapy in NSCLC (31).…”
Section: Introductionmentioning
confidence: 99%
“…Then, the same authors combined the previously described Delta Radiomic model with a widely used clinical biomarker for pancreatic cancer (CA19-9), demonstrating how the integration of the two predictors leads to more reliable predictive performance than considering the individual parameters alone [ 43 ].…”
Section: Discussionmentioning
confidence: 99%